A Summary of N, P, and K Research with Potato in Florida - George Hochmuth; Ed Hanlon (EDIS)
Potato fertilization research has been conducted in Florida for more than sixty years. During this time, changes have occurred in potato production practices including new cultivars, refinements in fertilizer application timing, use of fertilizer recommendations based on soil nutrient analysis, use of nematicides, and improved weed and pest management practices. This revised 33-page fact sheet summarizes potato fertilization research leading to current University of Florida recommendations and summarizes needs for additional research. Written by George Hochmuth and Ed Hanlon and published by the UF Department of Soil and Water Science, April 2011.